Monitoring Land Use Change and Vegetation Dynamics by Remote Sensing in the Steppe Region of Sidi Bel Abbes (Northwest, Algeria) - Zerey, Wael El; Gael, Mamfoumby; Zerey-Belaskri, Asma EL (International Journal of Environment, 2017)
The application of remote sensing in land cover changes monitoring is a very efficient tool, for landscape management in arid regions. To assess the spatial-temporal dynamics, of egetation, in the southern region of Sidi Bel Abbes, for the period (2001- 2014), Landsat and MODIS NDVI data were processed and analysed using remote sensing software. The obtained results, confirm that the steppe region is highly degraded in the south and in the south-east, with light progression of vegetation noticed in the north and the north-west of the study area. The increase of vegetation cover is related to the reforestation actions, engaged by the forest services. For decision makers, the use of satellite imagery can improve the strategic conservation and management plans of the steppe ecosystem. International Journal of Environment Volume-6, Issue-3, Jun-Aug 2017, Page:71-81